2012
DOI: 10.1016/j.ijrobp.2011.03.046
|View full text |Cite
|
Sign up to set email alerts
|

Novel Assessment of Renal Motion in Children as Measured via Four-Dimensional Computed Tomography

Abstract: Purpose Abdominal intensity-modulated radiation therapy and proton therapy require quantification of target and organ motion to optimize localization and treatment. Although addressed in adults, there is no available literature on this issue in pediatric patients. We assessed physiologic renal motion in pediatric patients. Methods and Materials Twenty free-breathing pediatric patients at a median age of 8 years (range, 2-18 years) with intra-abdominal tumors underwent computed tomography (CT) simulation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 17 publications
2
55
0
Order By: Relevance
“…Multiple respiratory traces were obtained and reconstructed through 8 respiratory phases. These 8 phases were exported to the Siemens multi-modality workstation for evaluation by InSpace software [4]. …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple respiratory traces were obtained and reconstructed through 8 respiratory phases. These 8 phases were exported to the Siemens multi-modality workstation for evaluation by InSpace software [4]. …”
Section: Methodsmentioning
confidence: 99%
“…For the actual treatment plan (IMRT_phys), we used an ITV surrounding the CTV and accounting for physiologic organ motion of 1 mm radially and inferiorly and 4 mm superiorly. Although no class solution works for all cases, a near-class solution was found suitable for each of these 8 cases on the basis of individual review of 4DCT data and estimation of renal motion in these uniformly young children [4]. In each patient, the adjacent renal organs served as surrogates to estimate the tumor bed/target motion due to the retroperitoneal/adrenal primary location of each tumor bed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pai Panandiker et al (42) analyzed kidney motion data for children undergoing anesthesia (2-8 years of age) and showed that kidney motion for this age group was less than 2 mm for both the right and left kidneys. The older age group (9-18 years of age), not under general anesthesia, showed mean motion of 3.9 and 3.07 mm for the right and left kidneys respectively.…”
Section: Kidney Motion In Pediatric Patientsmentioning
confidence: 99%
“…Only the abdominal motion of the diaphragm was moderately correlated with that of the kidney (23). However, even this potential surrogate was demonstrated to be unreliable in predicting the kidney position in pediatric patients (24). Interestingly, the same study demonstrated that the amount of motion in the cranio-caudal direction increases with age, while the motion in the lateral direction increases with height.…”
Section: Motion In Whole-body Imaging Studies: Sources and Magnitudementioning
confidence: 99%